Incidence of cancer among residents of high temperature geothermal areas in Iceland: a census based study 1981 to 2010 - Kristbjornsdottir Adalbjorg; Rafnsson Vilhjalmur (Environmental Health, 2012)
Abstract Background Residents of geothermal areas are exposed to geothermal emissions and water containing hydrogen sulphide and radon. We aim to study the association of the residence in high temperature geothermal area with the risk of cancer. Methods This is an observational cohort study where the population of a high-temperature geothermal area (35,707 person years) was compared with the population of a cold, non-geothermal area (571,509 person years). The cohort originates from the 1981 National Census. The follow up from 1981 to 2010 was based on record linkage by personal identifier with nation-wide death and cancer registries. Through the registries it was possible to ascertain emigration and vital status and to identify the cancer cases, 95% of which had histological verification. The hazard ratio (HR) and 95% confidence intervals (CI) were estimated in Cox-model, adjusted for age, gender, education and housing. Results Adjusted HR in the high-temperature geothermal area for all cancers was 1.22 (95% CI 1.05 to 1.42) as compared with the cold area. The HR for pancreatic cancer was 2.85 (95% CI 1.39 to 5.86), breast cancer 1.59 (95% CI 1.10 to 2.31), lymphoid and hematopoietic cancer 1.64 (95% CI 1.00 to 2.66), and non-Hodgkins lymphoma 3.25 (95% CI 1.73 to 6.07). The HR for basal cell carcinoma of the skin was 1.61 (95% CI 1.10 to 2.35). The HRs were increased for cancers of the nasal cavities, larynx, lung, prostate, thyroid gland and for soft tissue sarcoma; however the 95% CIs included unity. Conclusions More precise information on chemical and physical exposures are needed to draw firm conclusions from the findings. The significant excess risk of breast cancer, and basal cell carcinoma of the skin, and the suggested excess risk of other radiation-sensitive cancers, calls for measurement of the content of the gas emissions and the hot water, which have been of concern in previous studies in volcanic areas. There are indications of an exposure-response relationship, as the risk was higher in comparison with the cold than with the warm reference area. Social status has been taken into account and data on reproductive factors and smoking habits show that these do not seem to explain the increased risk of cancers, however unknown confounding can not be excluded.